Differences in spontaneous speech fluency between Parkinson's disease and spinocerebellar ataxia type 3 - dos Santos, Vanessa Brzoskowski; Ayres, Annelise; Kieling, Maiara Laís Mallmann; Miglorini, Elaine Cristina; Jardim, Laura Bannach; Schumacher-Schuh, Artur Francisco; Rieder, Carlos Roberto de Mello; Castilhos, Raphael Machado de; Spencer, Kristie; Rothe-Neves, Rui; Olchik, Maira Rozenfeld (Frontiers in Neurology, 2023)
Background: The basal ganglia and cerebellum both have a role in speech production, although the effect of isolated involvement of these structures on speech fluency remains unclear. Objective: To assess the differences in the articulatory pattern in patients with cerebellar versus basal ganglia disorders. Methods: Twenty individuals with Parkinson's disease (PD), 20 with Spinocerebellar Ataxia type 3 (SCA3), and 40 controls (control group - CG) were included. Diadochokinesis (DDK) and monologue tasks were collected. Results: The only variable that distinguished SCA3 carriers from the CG was the number of syllables in the monologue, with SCA3 patients having a significantly lower number). For patients with PD, the number of syllables, phonation time, DDK, and monologue were significantly lower than for the CG. Patients with PD were significantly worse compared to patients with SCA3 in the number of syllables and phonation time in DDK, and phonation time in monologue. Additionally, there was a significant correlation between the number of syllables in the monologue and the MDS-UPDRS III for participants with PD, and the Friedreich Ataxia Rating Scale for participants with SCA3 suggesting a relationship between speech and general motor functioning. Conclusions: The monologue task is better at discriminating individuals with cerebellar versus Parkinson’s diseases as well as differentiating healthy control and was related to the severity of the disease.